Knowledge and Health Problems Related to Health Behavior among the Secondary School Children in Rural Community of Dhamrai Upazila, Dhaka - Rahman, MM; Rahman, A; Sajoni, TT; Kabir, SB; Nahar, J; Mehrin, F (Anwer Khan Modern Medical College Journal, 2014)
In Bangladesh, there are 18,756 secondary schools in which 17.91 million students are enrolled. School children are more vulnerable to be attacked by various types of communicable diseases due to poor health behaviors. The aim of this study was to find out knowledge and health problems related to health behavior among the secondary school children. This descriptive cross sectional study was carried among 795 secondary school children by purposive sampling from 22nd to 24th January 2014 in different school s of Dhamrai Upazila, Dhaka. Data were collected on a pretested questionnaire by face to face interview. Data were analyzed manually and by using computer. The study revealed that majority of the respondents were Muslims by religion, 45% had education level Class VII and mean age was 13±1.7 years. Most of them 45% & 40% students father's and Mothers education level respectively was HSC and above. About 50% students father's occupation were service and 33% were businessman. Mostly about 79% students mother's were housewife. Among all about 71% students were found having 2-3 brothers and sisters respectively. About 20%, 9% and 7% respondents don't agree on drinking clean boiled water, avoidance of smoking and care of nails as a healthy behavior. 25%, 13% and 11% respondents don't practice drinking clean boiled, regular brushing of teeth and care of nails. About 95%, 74% and 67% learned on health behavior from family teachers and text books respectively. About 19%, 14% and 10% students were suffering from common cold, unhealthy hair and itching respectively. Knowledge regarding health behavior among the secondary school children was found still worse. The study recommends more effective implantation of awareness program to improve knowledge regarding health behavior. DOI: http://dx.doi.org/10.3329/akmmcj.v5i2.21127 Anwer Khan Modern Medical College Journal Vol. 5, No. 2: July 2014, Pages 18-22